Governance in World Affairs - Young, Oran R. (Book collections on Project MUSE., 1999)
In this book Young extends and generalises his earlier work on international environmental regimes to present a comprehensive account of the current status and future prospects of regime theory as a way of thinking about governance in world affairs.